Sistematización del empleo de biomarcadores en el diagnóstico y seguimiento de pacientes con insuficiencia renal - Chipantiza Maliza, Joselyn Nicole (2022)
ABSTRACT: The purpose of this research topic was to analyze the use of biomarkers in a patient's diagnosis and monitoring of renal insufficiency through documentary analysis and bibliographic review that help to contextualize the disease. A biomarker is a measurable indicator of a specific biological state, particularly one relevant to the risk, presence, or stage of the disease. The use of biomarkers in the diagnosis and monitoring of patients with renal insufficiency was investigated. The research methodology is qualitative, with a phenomenological approach and a descriptive scope. The technique selected for the data collection process is documentary analysis. For the development of the research sample, 25 articles were selected that fulfill the inclusion and exclusion criteria. The results show the use of 23 biomarkers, where serum creatinine is the preferred laboratory test, the glomerular filtrate for a specific detection according to each case, and the preliminary diagnosis of renal insufficiency. To conclude, the biomarkers used in the diagnosis and monitoring of patients with renal insufficiency help to determine specific treatments according to each case and provide information on the critical level of progression. Moreover, the systematization shows that the most frequently used biomarkers are serum creatinine and glomerular filtration. There is a consensus on considering Cystatin C as a biomarker for early diagnosis. The search for a suitable marker is ongoing because they are associated with certain limitations but show valuable contributions.